Assessment the Medical Sciences Students` Knowledge and Skill About Basic Cardiopulmonary Resuscitation (CPR) in Accidents and Disasters - Mohsen Saffari*; Najmemolouk Amini; Amir H Pakpour; Hormoz Sanaeinasab; Hojat rahidi jahan (Iranian Association of Health Education and Health Promotion, 2013)
Background:The study aimed at assessing the knowledge and skill of 4 medial related majors regard to CPR. Methods: Using a the descriptive - analytical design , the knowledge and skill of 320 senior students in medicine and nursing (clinical) disciplines with special education about CPR and health management & public health students (non-clinical) with potential related education about CPR during educational course, were assessed by a self report questionnaire. Collected data were analyzed by Chi 2 or Fisher, Student t and ANOVA tests in SPSS software. Results: Most of participants were female. The mean age of sample was 22.5±2.92. Students which receive special education about CPR, compared to other disciplines that receive only related education about CPR, have more knowledge about it (p< 0.001) but their knowledge has a considerable gap to ideal situation. The score related to reported skills by most of student was higher than their knowledge score. Conclusion: The findings of this study indicate although the most of clinical participants versus non clinicians have relatively good knowledge about CPR but there is an over estimation between knowledge and skills related to CPR among them. This needs to more assess as well as the need to revision in special related education.